Comparative susceptibility to atrazine of three developmental stages of Bufo arenarum (amphibia: anura) and influence on metamorphosis: non-monotonous acceleration of the time to climax and delayed tail resorption - Brodeur, Celine Marie Julie (2009)
Acute and subchronic toxicity of atrazine was evaluated in embryos (stage 4) and in premetamorphosis (stage 25) and prometamorphosis (stage 38¡V39) larvae of the common South American toad Rhinella arenarum (Anura: bufonidae). The influence of atrazine on the last stages of metamorphosis was also examined by exposing prometamorphosis larvae until completion of metamorphosis. Results obtained revealed that larvae in premetamorphosis are more sensitive than larvae in prometamorphosis and that these are, in turn, more sensitive than embryonic stages. Indeed, concentrations of atrazine as high as 30 mg/L had little effects on embryonic stages, the embryos surviving and developing in a similar manner as controls. LC50s of premetamorphosis larvae equaled 27.16, 7.03 and 2.32 mg/L of atrazine after 4, 14 and 21 days of exposure, respectively, compared to LC50s values of 18.27 and 14.43 mg/L after 14 and 21 days of exposure for larvae in prometamorphosis. In experiments with premetamorphosis larvae, the range of tested concentrations was extended to very low concentrations (down to 0.0001 mg/L) to examine whether recent findings of greater mortality at lower doses than at higher doses were also observed in R. arenarum but no such pattern was found. Exposure of prometamorphosis larvae to concentrations of atrazine of 10 mg/L and above widely prevented completion of metamorphosis and caused important mortality. Alternatively, whereas all animals eventually completed metamorphosis when exposed to concentrations of atrazine between 0.1 and 5 mg/L, the timings of metamorphosis were altered starting from 0.1 mg/L, the lowest concentration tested. Indeed, a significant decrease in the time needed for 50% of the larvae to reach the metamorphic climax (stage 42) was observed within this range of atrazine concentrations, the response presenting a U-shaped non-monotonic dose¡Vresponse curve. Larvae exposed to these concentrations of atrazine also needed significantly more time for completing tail resorption, this effect being equivalent at all concentrations. Overall, the combination of these two different facets of atrazine influence on metamorphosis resulted in a significant acceleration of metamorphosis at 1 mg/L and a significant increase in the duration of metamorphosis at 5 mg/L, whereas no significant difference was observed with 0.1 mg/L.